Impact of the Diabetes Inpatient Care and Education (DICE) project and the DICE Care Pathway on patient outcomes and trainee doctor's knowledge and confidence. Issue 7 (10th April 2015) - Rajendran, R.; Kerry, C.; Round, R.‐M.; Barker, S.; Scott, A.; Rayman, G.; the DICE team
Abstract Aim To evaluate the impact of the Diabetes Inpatient Care and Education project and a comprehensive diabetes care pathway, the Diabetes Inpatient Care and Education Care Pathway, on patient outcomes and on the knowledge and confidence of trainee doctors. Methods The effect on patient outcomes was evaluated by comparing the National Diabetes Inpatient Audit data before (2012) and after (2013) implementing the Diabetes Inpatient Care and Education project. The impact on trainee doctors was evaluated using the Modified Kirkpatrick model. Just before the project began and again 3 months later, trainee doctors were surveyed to assess their knowledge and confidence in inpatient diabetes care. Results Patient harm was found to have been reduced significantly when National Diabetes Inpatient Audit data for 2012 and 2013 were compared. Severe hypoglycaemia decreased from 15.4 to 9.7%, medication errors from 56.9 to 21.1% and insulin errors from 31 to 7%. Across the 96 trainee doctors surveyed, the mean (sd) knowledge and confidence scores increased significantly (P < 0.001 for both) from 57.1 (16.8) and 61.8 (14.9) to 68.4 (13.3) and 74.3 (11.7), respectively. Conclusion The Diabetes Inpatient Care and Education project and the Diabetes Inpatient Care and Education Care Pathway improved patient outcomes and the knowledge and confidence of trainee doctors in this hospital. The impact of a similar project in other hospitals needs to be evaluated.